Enhanced Store-Operated Ca2+ Signal of Small Intestinal Smooth Muscle Cells Accelerates Small Bowel Transit Speed in Type 1 Diabetic Mouse - Dai, Fang; Guo, Jizheng; Wang, Yang; Jiang, Tian; Chen, Hongbo; Hu, Ying; Du, Juan; Xia, Xianming; Zhang, Qiu; Shen, Bing (Frontiers in Physiology, 2021)
Aims: The underlying mechanism of diabetic enteropathy, a common complication of type 1 diabetes, remains unclear. Store-operated Ca2+ entry (SOCE) is a ubiquitous type of Ca2+ influx involved in various cellular functions. Here, we show that SOCE-related stromal interaction molecule 1 (STIM1) and Orai1 participate in inappropriate cellular Ca2+ homeostasis, augmenting agonist-induced small intestinal smooth muscle contraction and small bowel transit speed in a mouse model of type 1 diabetes. Methods and Results: We used small interfering (si)RNA to suppress STIM1 and Orai1 proteins, and employed intracellular Ca2+, small intestinal contraction and intestinal transit speed measurement to investigate the functional change. We found that SOCE activity and Orai1 and STIM1 expression levels of small intestinal smooth muscle were significantly increased in cells cultured in high glucose medium or in diabetic mice. Gastrointestinal transit speed and SOCE-mediated contractions were markedly increased in diabetic mice; Knocking down Orai1 or STIM1 with siRNA rescued both alterations in diabetic mice. However, the Orai1-large conductance Ca2+-activated K+ (BKCa) channel interaction was decreased in diabetic mice, and suppressing Orai1 expression or inhibiting the BKCa channel increased agonist-induced small intestinal contractions in normal mice. Conclusions: We concluded that the increased SOCE caused by excessive STIM1 and Orai1 expression and decreased Orai1-BKCa interaction augmented small intestinal smooth muscle contraction and accelerated small bowel transit speed in diabetic mice. This finding demonstrates a pathological role for SOCE in diabetic enteropathy and provides a potential therapeutic target for diabetic enteropathy.